Factors Affecting Lethality of Bisphenol a on Biomphalaria alexandrina Snails - Sara A Mansour; Maha FM Soliman; Fatma AA El Deeb; Nahla S El-Shenawy (International Journal of Veterinary Science and Research - Peertechz Publications, 2016)
The present study was undertaken to investigate the influence of some environmental factors including temperature, water vegetation, bed mud and pH on LC50, LC90 and LT50 of bisphenol A (BPA) on the snail host of Schistosoma mansoni, Biomphalaria alexandrina. Effects of exposure to the sublethal concentrations of BPA on some biological aspects of the snails and on the cercarial output form S. mansoni infected snails were studied. Results showed that temperature, water vegetation, bed mud and pH markedly affected the lethality of BPA. The biological parameters of B. alexandrina including survival rate, egg hatchability and egg laying capacity were greatly affected by exposure to BPA and the response was dose dependent. Regarding the possible effect of BPA on transmission of schistosomiasis, results showed that exposure to different concentration of BPA for 7 days before miracidial infection caused the death of all the snails before reaching the patent period while, no cercarial output was recorded from snails exposed to BPA for 24 hrs till their death. In conclusion, our results showed that the environmental characteristics may alter the biological impacts of BPA and the exposure of snail to BPA may affect the transmission of schistosomiasis.